1, 3‐Propanediol adsorption on a cation exchange resin: Adsorption isotherm, thermodynamics, and mechanistic studies. Issue 5 (30th June 2014) - Wang, Shizhen; Dai, Hongfei; Yan, Zhengping; Zhu, Chunjie; Huang, Lingfeng; Fang, Baishan
<x xml:space="preserve">Abstract</x> 1, 3‐Propanediol (1, 3‐PD) is widely used in cosmetics, foods, antifreezes, and polyester. A low‐cost cation exchange resin, 001×7 H‐form resin, was selected for 1, 3‐PD adsorption obtained from microbial fermentation of crude glycerol. The thermodynamics and kinetics of adsorption were studied. To identify the characteristics of the adsorption process, the influence of 1, 3‐PD concentration, temperature, and resin particle diameters was studied. The temperature dependence of the adsorption equilibrium in the range of 288 to 318 K was observed to satisfy the Langmuir isotherm well. The thermodynamic parameters, adsorption enthalpy, entropy, and Gibbs free energy, were determined as 36.2 kJ·moL−1, 160 mol−1·K−1, and −11.2 kJ·moL−1, respectively, which indicated that the adsorption was spontaneous and endothermic. The adsorption kinetics was accurately represented by the shell progressive model and indicated that the particle diffusion was the rate‐limiting step. Based on the kinetic simulation, the rate constant of exchange (k0), order reaction (α), and the apparent activation energy reaction (Ea) were obtained as 3.11×10−3, 0.644, and 11.5 kJ·moL−1, respectively. This kinetic and thermodynamic analysis of 1, 3‐PD recovery presented in this article is also applicable for the separation of other polyols by resin adsorption, which will promote value‐added utilization of glycerol.